Manajemen Pesantren dan Pembentukan Perilaku Santri - Muhammadiyah Yunus (Al-Riwayah : Jurnal Kependidikan, 2015)
In responding to modernity, indeed, education including Islamic education is supposed to consider socio-cultural frameworks. Pesantren which resembles madrasa or a religious school elsewhere in the Islamic world, seem to have been of some interest to Western scholars. The evidence can be seen from some books published by western writers. Indonesian scholars, on the other hand, have produced an enormous literature, including countless books and scholarly theses. A large number of these works assert that pesantren and modernity are not incompatible but can work together for the betterment of the nation. The discourse on cultural and social change has influenced all aspects of life including the orientation of education, social ethics approach and values system of the pesantren. Considering that socio-cultural changes are a learning process, then religious education, especially represented by pesantren, can take part in socio-cultural roles. One unique characteristic of moderate pesantrens which has enabled them to produce tolerant and pluralistic people is their balance in teaching Islamic legal aspects (Fikih) and the spirituality (Sufism). As aresult, they produce people with an exclusionary stance who see the world as black and white and who lack the beauty and inner meaning of the religion: peace, tolerance, respect, love and care for others, and other esoteric and humanitarian traits.